(3GdJHjGf djGbhJg GdEjeGf hhGSWI GdHQgGfs - (3GdMSf Hf eMeO Hf eMeO Hf CHi HcQ GdQUGUs; (3CHh GdaVd GdYHGS Hf TQhjfs
(3ChdgG (B:s
(3Chd GdLRA GdChd efg eHJhQ , hChd eG ajg bhdg (B: (3Cf jchf KHhJg HGdaGYd , heJi bjd Cf chfg eJMjRkG YfOce jba Ydi UaI CNQi s
(3BNQgG (B:s
(3hBNQ GdLRA GdKGfi efg bhdg (B: (3Ch EfeG cGfhG jbUQhf YfO PcQg ddg hMOg ai ZjQ GdhbJ GdPi jefYge Gddg SHMGfg ef SeGY GdbQBf efg ai UdGJg cjdG jDPhg Ydjg hBdg hSde s
(3JHUQI GdYfhGf (B:s
(3LeYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdeYGQa GdYGeIs